2016
DOI: 10.1002/ange.201606960
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Microfluidic Fabrication of Polyelectrolyte Microcapsules in Aqueous Conditions for Protein Release

Abstract: We report am icrofluidic approach for one-step fabrication of polyelectrolyte microcapsules in aqueous conditions.U sing two immiscible aqueous polymer solutions,w e generate transient water-in-water-in-water double emulsion droplets and use them as templates to fabricate polyelectrolyte microcapsules.T he capsule shell is formed by the complexation of oppositely charged polyelectrolytes at the immiscible interface.W ef ind that attractive electrostatic interactions can significantly prolong the release of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 35 publications
(21 reference statements)
0
25
0
Order By: Relevance
“…The hemispherical shells shrank and wrinkled in high vacuum, which was typical of polymeric hollow capsules and vesicles made through other methods. 27 Using a confocal laser scanning microscope (CLSM), we were able to further characterize hemispherical shells in 3D (Figure 2e and 2f). Because gravity oriented the Janus droplets with denser fluorous phase downward, we proved that the interfacial polymerization only occurred at the hydrocarbon-water interface because only the top hemisphere in Figure 2e emitted green fluorescence.…”
Section: Characterization Of Polymeric Hemispherical Shellmentioning
confidence: 99%
“…The hemispherical shells shrank and wrinkled in high vacuum, which was typical of polymeric hollow capsules and vesicles made through other methods. 27 Using a confocal laser scanning microscope (CLSM), we were able to further characterize hemispherical shells in 3D (Figure 2e and 2f). Because gravity oriented the Janus droplets with denser fluorous phase downward, we proved that the interfacial polymerization only occurred at the hydrocarbon-water interface because only the top hemisphere in Figure 2e emitted green fluorescence.…”
Section: Characterization Of Polymeric Hemispherical Shellmentioning
confidence: 99%
“…These results indicated that at low concentrations (5% (w/w)) of both DEX and PEG, it was difficult to generate droplets. However, when the concentrations of two solutions were increased to 10% (w/w), stable droplets were started to form even with lower molecule weight, compared to existing literature . Moreover, monodispersed droplets were easier to be generated when the concentrations of DEX and PEG were increased to more than 10% (w/w).…”
Section: Resultsmentioning
confidence: 69%
“…The W/W system is formed when concentrations of two components are above a critical value due to the domination of the system's energy of interaction over the Gibb's free energy of mixing . The biocompatibility of W/W emulsions has been previously reported to fabricate polyelectrolyte microcapsules for the delivery of proteins without impairing their biological activities . Unfortunately, these W/W systems possess a very low interfacial tension (less than 10 −4 N m −1 ), which limits the stable and controllable generation of droplets via microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric microcapsules as containers/carriers can be used for self-healing coating, [1][2][3] sensors, 4,5 phase change materials, 6 controlled release of drugs and pesticides, [7][8][9][10][11][12][13] pressure-sensitive switches, 14 displays or smart windows, 15,16 optical materials, 17 enzyme immobilization, 18 and fragrances 19 . Microcapsules can protect active cargoes against environmental hazards (such as moisture, oxidation and bacteria), and thus increase their shelf life.…”
Section: Introductionmentioning
confidence: 99%